Modelling an impact of enterprises’ investment activity on the level of a region’s sustainable development using fuzzy logic apparatus - Korytko, T.Y.; Kruk, O.M. (Економіка промисловості, 2021)
The paper examines the essence of sustainable development of a region. It has been noted that achievement of sustainable development of a region is possible under the condition of plurality of transformations and changes in enterprises, institutions, organizations, and societies, which operate in the region. The study proves that the assessment of sustainable development of the region, considering the enterprises’ investment activity takes into account the following spaces: economic, territorial, administrative, demographic, institutional and organizational ones. Each of the above spaces can be assessed using indicators that characterize the peculiarities of the region.The objective of the article is to develop a scientific and methodological approach to modeling the impact of enterprises’ investment activity on the sustainable development of the region.The proposed approach to modeling the impact of enterprises’ investment activity on the sustainable development of the region allows: to analyze the quantitative indicators of the constituent elements and to define the state and level of development of each element, which significantly improves the efficiency of the necessary organizational support. Testing of the proposed model for assessing the impact of enterprises’ investment activity on the sustainable development of the region was demonstrated on the example of Donetsk region.Based on the apparatus of fuzzy logic, a hierarchical model of assessing the sustainable development of the region takes into account the investment activity of enterprises, which allows the use of expert information about the object of study in the form of logical rules; to synthesize quantitative indicators into a single integrated indicator of structural elements of the system. The advantage of the proposed method is its versatility.The study shows that during 2018-2020 the level of sustainable development of the Donetsk region based on enterprises’ investment activity was satisfactory (0.57). Also, it should be noted that there is a worsening in the value of the indicator, which requires adjustment of strategic guidelines of the region.